DEVELOPMENT OF SLINGSHOT BALL LEARNING MEDIA FOR EMOTIONAL DEVELOPMENT IN EARLY CHILDHOOD IN CEMPAKA KINDERGARTEN - Sulastya Ningsih; Elva M Sumirat; Nurul Aini MM Sodik; Sri Rawanti (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
Emotional development in children is a major factor that influences their attitudes, values, and behavior in the future. This development aspect requires special attention because it must be fostered from the beginning. This study aims to create a product that can be used as a means in the learning process, namely